PENGEMBANGAN SISTEM REALTIME MESSAGING AND NOTIFICATION DENGAN BOT TELEGRAM UNTUK PEMESANAN GEDUNG PADA WEBSITE E-COMMERCE SILUNGKANG.ID - Rizky Adji Pangestu; Atang Susila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Bots are software that is given orders to carry out tasks automatically via the internet, usually bots are given commands that are similar to activities or tasks performed by humans. The benefit of bots is to facilitate repetitive human tasks, such as sending emails to customers regularly, providing data reports to facilitate monitoring of servers or applications, and so on. In this study, bots are used as a solution to problems in the process of ordering buildings or products on the silungkang.id website. Bots are used by authors to have automatic conversations with customers and provide order notifications for admins to facilitate monitoring of the building or product ordering process. The author uses a bot system because it can reply to messages or send notifications in real time without having to wait for action from the admin.